Tropical spastic paraparesis in Kerala, South India - Oomman A, Madhusoodanan M (Neurology India, 2003)
Tropical Spastic Paraparesis (TSP) is an uncommon myeloneuropathy with an insular geographic distribution. In 1985, Human T-lymphotropic virus type I (HTLV-1) was reported to be a possible etiological factor.1 We did an epidemiological, clinical and virological study of 25 cases of TSP. They were predominantly young adult men, whose duration of illness ranged from 6 months to 15 years. Difficulty in walking, stiffness of legs and paraesthesia of legs were the main symptoms. None had tuberculosis, syphilis, malnutrition or lathyrism. Pyramidal signs of the lower limbs, upper limbs, posterior column involvement and spinothalamic tract dysfunction were the common signs. Laboratory findings and cerebrospinal fluid analysis were normal in most. Myelograms or MRI were normal in all. Only 1 case repeatedly tested positive for HTLV-1 antibodies. None of his relatives had clinical or virological evidence of TSP or HTLV-1 infection. Based on our study, we could not link HTLV-I infection to TSP in Indian cases. Virological testing for HTLV-I infection by polymerase chain reaction may be a better tool to reveal such an association. Our cases were similar to seronegative spinal spastic paralegia. A related new retrovirus or an altered immune response to HTLV-1 due to environmental or dietary factors are possibilities which require further exploration